FUNGSI RAGAM BAHASA PENJUAL IKAN DI PASAR OKA LAMAWALANG, KECAMATAN LARANTUKA, KABUPATEN FLORES TIMUR - Rikardus Pande Pande; Rikardus Pande (JURNAL ILMIAH BAHASA DAN SASTRA, 2021)
This article describes the diversity of languages ​​formed by the development of society in various aspects of life which includes various social activities, such as trade, government, health, education, and religion. The variety of languages ​​has functions such as the variety of languages ​​used by fish sellers in Oka market, Lamawalang, Larantuka District, East Flores Regency which grows and develops especially among speakers of the fish seller community. This variety of languages ​​can be found when fish sellers offer their fish to buyers where there is language contact, between Indonesian and local languages. The functions of various languages ​​used by fish sellers in the Oka Lamawalang market, Larantuka District, East Flores Regency with the Oka Lamawalang dialect include (1) instrumental (directive) functions, such as seducing, convincing, and asking, (2) interactional or interaction functions, such as asking , forms of interaction in the form of rejection and forms of agreement interaction, (3) representational or representational (declarative) functions such as showing and expressing, (4) personal functions, such as joy and disappointment.